DIMETILSULFOKSID SEBAGAI ENHANCER TRANSPOR TRANSDERMAL TEOFILIN SEDIAAN GEL - Resty Annisa Damayanti; Tedjo Yuwono (Pharmaciana, 2013)
Dimethylsulfoxide (DMSO) has been intensively studied the 19th century. Thissubstance is used as a medicine and solve. It can also be used as an absorptionenhancer of various drugs, either synthetical or herbal medicines. This study conductedwith DMSO as transdermal absorption enhancer of theophylline, which often used asan anti-cellulite dosage forms. The experiments studied in vitro transdermalabsorption of theophylline in gel dosage forms, containing 7% theophylline danvarious concentration of DMSO i.e. 0% , 3%, 5% and 7% DMSO respectively. Thesestudies used skin membrane of Wistar strain male rats in a vertical type diffusion Cell.The results indicated that DMSO was very potential as a permeation enhancertheophylline, the formula containing 7% DMSO increased the theophylline transportfrom 17,9 Âµg to 139,1 Âµg.